A Comparison of Maternal Attitudes to Breastfeeding in Public and the Association with Breastfeeding Duration in Four European Countries: Results of a Cohort Study. Issue 1 (22nd October 2014) - Scott, Jane A.; Kwok, Yin Ying; Synnott, Kate; Bogue, Joe; Amarri, Sergio; Norin, Elizabeth; Gil, Angel; Edwards, Christine A.; Other Members of the INFABIO Project Team
Abstract Background There is wide variation in the duration of breastfeeding across Europe which may in part be due to the between‐country differences in mothers' and societal attitudes towards breastfeeding in public. The objective of this study was to quantify and compare the maternal attitudes to, and practice of, breastfeeding in public in four European centers and investigate the association with duration of breastfeeding. Methods Participants (n = 389) were mothers recruited from maternity wards of hospitals in Glasgow (Scotland), Stockholm (Sweden), Granada (Spain), and Reggio‐Emilia (Italy). Results Among those who had breastfed, Scottish (adjOR 0.25 [95% CI 0.12–0.50]) and Italian mothers (adjOR 0.30 [95% CI 0.14–0.63]) were significantly less likely than Swedish mothers to have ever breastfed in public. Mothers who had a negative attitude toward breastfeeding in public were less likely to have ever breastfed in public (adjOR 0.05 [95% CI 0.02–0.17]), and those who had never breastfed in public were in turn more likely to discontinue breastfeeding earlier. Conclusions Perceived social norms may exert a stronger influence on breastfeeding outcomes than a woman's breastfeeding attitudes and knowledge. Differences between European countries in the duration of breastfeeding may be explained in part by differences in societal attitudes to breastfeeding in public.